2011
DOI: 10.1128/aem.05363-11
|View full text |Cite
|
Sign up to set email alerts
|

Novel Metagenome-Derived Carboxylesterase That Hydrolyzes β-Lactam Antibiotics

Abstract: It has been proposed that family VIII carboxylesterases and class C ␤-lactamases are phylogenetically related; however, none of carboxylesterases has been reported to hydrolyze ␤-lactam antibiotics except nitrocefin, a nonclinical chromogenic substrate. Here, we describe the first example of a novel carboxylesterase derived from a metagenome that is able to cleave the amide bond of various ␤-lactam substrates and the ester bond of p-nitrophenyl esters. A clone with lipolytic activity was selected by functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 33 publications
5
58
0
3
Order By: Relevance
“…Staphylococcus aureus ATCC Cultures of CA-S3F-1, PE-C-1 and PE-S2R-1 grown in the respective antibiotic (1 mg/mL)-containing LB broth at 26 • C with shaking overnight were diluted 1 in 10 in antibiotic (1 mg/mL)-containing LB broth and incubated for a further 4 h. The filtered (0.2 m filters), washed supernatants were used in the crude ␤-lactamase enzyme assays using nitrocefin at 100 M at a wavelength of 486 nm [16]. Escherichia coli transformed with pUC19 plasmid (AmpC ␤-lactamase-producing) was used as a positive control.…”
Section: Biological Activity Of the Antibiotic Solutions Following Inmentioning
confidence: 99%
“…Staphylococcus aureus ATCC Cultures of CA-S3F-1, PE-C-1 and PE-S2R-1 grown in the respective antibiotic (1 mg/mL)-containing LB broth at 26 • C with shaking overnight were diluted 1 in 10 in antibiotic (1 mg/mL)-containing LB broth and incubated for a further 4 h. The filtered (0.2 m filters), washed supernatants were used in the crude ␤-lactamase enzyme assays using nitrocefin at 100 M at a wavelength of 486 nm [16]. Escherichia coli transformed with pUC19 plasmid (AmpC ␤-lactamase-producing) was used as a positive control.…”
Section: Biological Activity Of the Antibiotic Solutions Following Inmentioning
confidence: 99%
“…The K m values determined for EstB3 and EstC7 were very low, suggesting high affinity for pNPB as a substrate. For comparison, K m values for other family VIII carboxylesterases from metagenome sources, such as those for EstC (58.7 M) (47) and EstU1 (6.0 M) (40), are in a similar range. The recently described esterase Cbotu_EstA, which is also capable of hydrolyzing PBAT, has a V max value similar to that of EstC7 (Cbotu_EstA V max ϭ 83.4 U mg Ϫ1 ); however, the K m value for Cbotu_EstA is 3 orders of magnitude higher (1.95 mM) (20).…”
Section: Figmentioning
confidence: 81%
“…4IVK) (39). Promiscuous ␤-lactamase activity has been demonstrated for some members of this family, such as the metagenome-derived carboxylesterases EstU1 (40) and Est22 (41), with first-generation cephalosporin-based derivatives. EstG4 clustered in family II of lipolytic enzymes, which show the conserved motif GDSL containing the active site serine.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, family VIII esterases are typically tested for their ability to hydrolyse a variety of β-lactam substrates ( Table 2). The majority either lack the activity or show negligible activity, despite the high sequence identity to the β-lactamases, while others have been described as exhibiting "promiscuous β-lactamase activity" [18,21,41,47,48,49]. Consequently, it has been suggested that these esterases have evolved from the class C β-lactamases, where some have maintained this remnant activity, while others have lost the capability due to steric interference resulting from structural evolution [18,41,50].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, detailed selectivity assays conducted for Est22 [49] and EstB [40] demonstrated that the enzymes selectively hydrolysed the ester bond of a number of cephalosporin-based substrates, while leaving the amide bond of the β-lactam ring intact. This clearly differentiates them from bona fide β-lactamases.…”
Section: Discussionmentioning
confidence: 99%